Characteristics of Dermatological and Venereological Diseases in Outpatients at Fatmawati Hospital From 2022 to 2024 - Meiuta Hening Prastiwi; Yufanti Sujudi (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2025)
Background: This research aimed to assess the characteristics and prevalence of dermatological and venereological diseases among outpatients at Fatmawati Hospital in Jakarta during the 2022-2024 period. Methods: A retrospective descriptive approach was employed, utilizing the total sampling method. Results: The findings reveal a consistent pattern in the ten most common diseases over the three-year period, including Dermatitis (31.22%), Morbus Hansen (17.03%), Psoriasis (11.70%), Acne Vulgaris (6.86%), Condyloma Acuminata (6.80%), Vitiligo (6.83%), Scabies (5.77%), Syphilis (5.17%), Tinea (4.73%), and Seborrheic Keratosis (3.87%). Conclusion: The research highlights the importance of Fatmawati Hospital as a key teaching institution for both general practitioners and specialists, due to the high number of dermatological and venereological cases observed during the research period. The presence of cases that could be managed at lower-level healthcare facilities also underscores the need for more effective referral systems.